PROFITABILITAS TERHADAP HARGA SAHAM MELALUI STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING: STUDY PADA SEKTOR OTOMOTIF DAN KOMPONENNYA DI BURSA EFEK INDONESIA - Kamaliyah, Wardatul; Prajawati, Maretha Ika; Sagena, Basir (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan, 2018)
The purpose of this study is to influence profit by means of intervening. The Population in this research is automotive sub sector and its component period 2012-2016 at Indonesia Stock Exchange. The type of this research is quantitative research, the sampling technique used purpusive sampling and testing is done by using path analysis, based on criteria that have been done then the number of samples obtained by 7 automotive companies and its components. The result of data analysis shows that profitability proxied with ROE has significant effect to capital structure, and capital structure proxyed by using LDER has significant influence to price, but profitability which is proxied ROE does not significantly take effect toward the stock price.